From criminalisation to harm reduction? The forms and functions of police drug diversion in England and Wales - Bacon, Matthew (Policing and society, 2024)
While drugs policing often involves enforcement interventions that seek to tackle drug offences and drug-related crime through criminal sanctions, it is becoming increasingly apparent that diversion now occupies a central position in police responses to people suspected of either simple possession or an offence related to their drug use. This article draws on findings from a qualitative study of police-led schemes in England and Wales to examine police perspectives on diversion, the rationales behind its various forms, and the problems it is designed to resolve. By giving a voice to the key police actors behind recent local initiatives, interview data reveals that the harmful impacts of criminal sanctions are a significant driver of schemes that divert people away from the criminal justice system and into support services. It is argued that the new wave of police drug diversion is a reaction against criminal justice interventions that emphasise punishment. Police drug diversion is conceptualised as a form of harm reduction policing that has the potential to reduce the adverse consequences of drug use, drug markets, and efforts to control them through the criminal justice system. A further important dimension of the present contribution concerns what diversion signifies about the police mission and broader trajectories in contemporary policing. Police drug diversion is situated within wider organisational shifts towards public health approaches to policing which aim to prevent crime and improve life chances by tackling unmet health, social and economic needs.